Comparison the effect of different irrigation on post-operative pain in cases with irreversible pulpitis (Mustansiria Dental Journal, 2024)
the aim of this study was to evaluate the effect of different types of irrigants  solution on postoperative pain after root canal treatment.Materials and method: 75 patients with irreversible pulpitis on the lower mandibular premolars teeth, after diagnosis  all cases were treated in a single visit  in a private clinic  over a period of 18 months. selected for this investigation endodontic treatment for the teeth using a wave one technique and then we divided the patients into 3 groups each group consist of 25 patients : in G.I irrigated with sodium hypochlorite (NaOCl).G.II  irrigated with chlorhixdine and GIII irrigated with NaOCl, followed by  EDTA 17% then CHX ( using conventional needle irrigation was performed with a 27-G (Appli-Vac) needle and syringe). The needle was placed short of the binding point or 2mm from the working length and irrigant was expressed over 30 seconds.)after irrigation the canals Will dried with paper point then obuterated it with guttapercha , a temporary filling covered the teeth after that   we asked the patient to record the postoperative pain after 6_12h , 24_48 h & one week , by using annual scale(AVS)the results show that the pain in G.III is the lowest pain than the other two groups.Conclusion the uses of the combination of irrigants solution resulting in less postoperative pain after endodontic treatment.The aim is to compare the effect of different irrigants solution on postoperative pain after root canal treatment.